Discovery and Biochemical Characterization of a Methanol Dehydrogenase From Lysinibacillus xylanilyticus - Lee, Jin-Young; Park, Sung-Hyun; Oh, So-Hyung; Lee, Jin-Ju; Kwon, Kil Koang; Kim, Su-Jin; Choi, Minjeong; Rha, Eugene; Lee, Hyewon; Lee, Dae-Hee; Sung, Bong Hyun; Yeom, Soo-Jin; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Bioconversion of C1 chemicals such as methane and methanol into higher carbon-chain chemicals has been widely studied. Methanol oxidation catalyzed by methanol dehydrogenase (Mdh) is one of the key steps in methanol utilization in bacterial methylotrophy. In bacteria, few NAD+-dependent Mdhs have been reported that convert methanol to formaldehyde. In this study, an uncharacterized Mdh gene from Lysinibacillus xylanilyticus (Lxmdh) was cloned and expressed in Escherichia coli. The maximum alcohol oxidation activity of the recombinant enzyme was observed at pH 9.5 and 55 °C in the presence of 10 mM Mg2+. To improve oxidation activity, rational approach-based, site-directed mutagenesis of 16 residues in the putative active site and NAD+-binding region was performed. The mutations S101V, T141S, and A164F improved the enzyme’s specific activity toward methanol compared to that of the wild-type enzyme. These mutants show a higher turnover rate than that of wild-type, although their KM values were slightly decreased compared to that of wild-type. Consequently, residues S101, T141, and A164 are related to catalytic activity in the active pocket for methanol dehydrogenation but not to substrate affinity. In conclusion, we characterized a new Lxmdh and its variants that may be potentially useful for the development of synthetic methylotrophy in the future.